Gender, educational attainment, and the impact of parental migration on children left behind - Francisca M. Antman (Institute for the Study of Labor (IZA), 2012)
Estimation of the causal effect of parental migration on children's educational attainment is complicated by the fact that migrants and non-migrants are likely to differ in unobservable ways that also affect children's educational outcomes. This paper suggests a novel way of addressing this selection problem by looking within the family to exploit variation in siblings' ages at the time of parental migration. The basic assumption underlying the analysis is that parental migration will have no effect on the educational outcomes of children who are at least 20 because they have already completed their educations. Their younger siblings, in contrast, may still be in school, and thus will be affected by the parental migration experience. The results point to a statistically significant positive effect of paternal U.S. migration on education for girls, suggesting that pushing a father's U.S. migration earlier in his daughter's life can lead to an increase in her educational attainment of up to 1 year relative to delaying migration until after she has turned 20. In contrast, paternal domestic migration has no statistically significant effect on educational attainment for girls or boys, suggesting that father absence does not play a major role in determining children's educational outcomes. Instead, these results suggest that the marginal dollars from U.S. migrant remittances appear to enable families to further educate their daughters. Thus, policymakers should view international migration as a potential pathway by which families raise educational attainments of girls in particular.
Keywords: O15; J12; J13; J16; J24; F22; 330; migration; father absence; education; gender; Väter; Internationale Wanderung; Rücküberweisung (Migranten); Kinder; Bildungsniveau; Migranten; Schätzung; USA